Model of occupational safety and health management of engineering enterprise - Москалюк, Андрей Юрьевич; Пурич, Валентина Николаевна (Technology audit and production reserves, 2015)
Society needs industrial technologies, it cannot exist without benefits of civilization like a utopian myth of a society without dangers and threats. Thus, the problem of occupational injuries will always exist, but it still requires a permit a better understanding of its causes, and, consequently, better methods of prevention. The model of project-based occupational safety and health management allows managing the processes of occupational safety of engineering enterprise, by evaluating the working environment of the enterprise and its level of labor protection for future projects of labor protection, which reduces the likelihood of accidents and / or accidents, as well as minimizing the effects of their occurrence Thus, the justification for the applicability of the design-oriented approach to occupational safety and health management of engineering enterprise suggests a proactive occupational safety and health management. The established relationship of categories of causes factors of injury / or accident in the enterprise: working conditions, work organization, natural (surrounding) factors of labor, psycho-emotional status of the staff and each employee, as well as the functional state of employee’ organism. This classification in conjunction with the factors of production and productive working environment allows for a logical conclusion about the need to project labor protection to its approach that is proactive management. The research results can be used by engineers in the field of occupational safety industrial safety, as well as decision support systems of engineering enterprises.